Norepinephrine transporter availability in brown fat is reduced in obesity: a human PET study with [(11)C] MRB - Sanchez-Rangel, Elizabeth (Int J Obes (Lond), 2019)
The energy-dissipating properties of brown adipose tissue (BAT) have been proposed as therapeutic targets for obesity and diabetes. Little is known about basal BAT activity. Capitalizing on the dense sympathetic innervation of BAT, we have previously shown that BAT can be detected in humans under resting room temperature (RT) conditions by using (S,S)-(11)C–O-methylreboxetine (MRB), a selective ligand for the norepinephrine transporter (NET). In this study, we determine whether MRB labeling of human BAT is altered by obesity. Fifteen healthy, nondiabetic Caucasian women (nine lean, age 25.6 ± 1.7, BMI 21.8 ± 1.3 kg/m(2); six obese age 30.8 ± 8.8 BMI 37.9 ± 6.6 kg/m(2)) underwent PET-CT imaging of the neck/supraclavicular region using (11)C-MRB under RT conditions. The distribution volume ratio (DVR) for (11)C-MRB was estimated via multilinear reference tissue model 2 (MRTM2) referenced to the occipital cortex. Two women (one lean and one with obesity) had no detectable BAT. Of the women with detectable BAT, women with obesity had lower (11)C-MRB DVR (0.80 ± 0.12 BAT DVR) compared to lean (1.15 ± 0.19 BAT DVR) (p = 0.004). Our findings are consistent with reports that NET is decreased in obesity and suggest that the sympathetic innervation of BAT is altered in obesity.